The Concept and Practice of Childfree in Tafsir Al-Misbah - Tsuraya, Salma Fahriya; Iswahyudi, Iswahyudi (AL-TAHRIR, 2024)
Childfree is the view of married couples who decide not to have children. Childfree also became the talk of the Indonesian people when Gita Savitri, an influencer promoted the childfree campaign in Indonesia. Childfree has two perspectives: some view childfree as something that is allowed, and some reject it. In addition to causing various perspectives among the public, childfree also causes differences of opinion among people who are experts in Islamic science. Therefore, with the differences in opinions, views, and laws, the author is interested in making childfree a research problem that needs to be discussed. According to the Qur'anic verses, the author chose Tafsir Al-Mis}ba>h} to find the perspective of childlessness. The purpose of this research is to complement the shortcomings of previous studies from the religious side. Data processing in this article is through the tah}li>li> method. The tah}li>li> method itself is an analysis of the verses of the Qur'an studied from one verse, or letter, whose order is adjusted to the systematics of the Uthma>ni> mush}af. Tafsir Al-Mis}ba>h} views children from three perspectives, namely lust, humans are created in pairs, and children are sustenance.